Consequência lógica e modelos: Uma investigação lógico-filosófica - Martins, Ícaro Coelho (2021)
The goal of this work is to accomplish a logical-philosophical investigation on the logical consequence. More specifically, we are going to analyze the logical consequence from the view of Model Theory, i.e., we are going to analyze logical consequence from the model-theoretic perspective. Because of this methodological approach, our investigation will begin with the fundamental locus of model-theoretic logical consequence, which is the Metamathematical work of the polish mathematician and logician Alfred Tarski. Tarski's model-theoretical proposal, in turn, given its great influence, ended up eclipsing the logical consequence tout court. The logical consequence turned out to be nothing less than the model-theoretical consequence. It is in this context that the sed contra the model-theoretic proposal emerges, condensed in John Etchemendy's criticisms. However, such criticisms produced conservative and revisionist responses regarding the model-theoretical proposal. Therefore, this work, taking advantage of this dialectical context, seeks to undertake a logical-philosophical investigation that allows the preliminary articulation of a theory of logical consequence\truth. This being the case, first, we present Tarski's treatment of logical consequence, articulated in three levels: logical consequence as an operator, as a proof-theoretical notion, and as a model-theoretic notion. Accordingly, we present and evaluate John Etchemendy's criticisms, along with the responses to his criticisms. In the next chapter, we present three theoretically substantive revisionist proposals. In the last chapter, we tried to articulate a synthesis of this dialectical context that allows us to outline an inchoative theory of logical consequence.